Microscopic colitis in older adults: impact, diagnosis, and management - Istvan Fedor; Eva Zold; Zsolt Barta (SAGE Publishing, 2022)
Microscopic colitis (comprising lymphocytic and collagenous colitis, albeit an incomplete variant is gaining recognition as well) is a chronic, immune-mediated inflammatory state of the lower gastrointestinal tract (colon). The diagnosis requires diagnostic colonoscopy with characteristic histopathological findings. They have a propensity to present in senior populations (above 60 years of age), particularly women - who are approximately 2.5-3 times more likely to develop microscopic colitis. Preexisting other immune-inflammatory diseases are also shown to predispose patients for the development of microscopic colitis. The classic presentation is profuse watery diarrhea, often during the night or early morning hours. Fecal incontinence and abdominal pain are frequent as well. Thus, the disease impacts patients' quality of life and well-being. The first described cases date back to the seventies and eighties of the twentieth century, thereby they can be considered fairly recently discovered disease states. Our understanding of the disease and its pathophysiology is still incomplete. Although there is a lack of unified recommendation for treatment, most clinicians prefer the use of budesonide, and most published guidelines regard this locally acting glucocorticoid as the therapy of choice. In our article, we aimed for a brief, noncomprehensive overview of the clinical significance, diagnosis, and management of microscopic colitis.